New Zealand Eriophyoidea (Acari: Prostigmata): an update with descriptions of one new genus and six new species - Xue, Xiao-Feng; Zhang, Zhi-Qiang (Zootaxa, 2008)
The New Zealand fauna of Eriophyoidea (Acari: Prostigmata) is updated with a checklist. One new genus, six new species, three new combinations, one new record and some new distribution records of eriophyoid mites from New Zealand are described and illustrated, namely Disella rebeeveri sp. nov. on Kunzea ericoides (Myrtaceae); Cecidophyopsis hendersoni (Keifer, 1954), rec. nov. on Yucca glauca and Y. elephantipes (Agavaceae); Nameriophyes sapidae gen. nov. & sp. nov. on Rhopalostylis sapida (Palmae); Eriophyes bennetti sp. nov. on Fuchsia excorticata (Onagraceae); Eriophyes georgeae sp. nov. on Brachyglottis elaeagnifolia (Asteraceae); Aceria flynni sp. nov. on Kunzea ericoides (Myrtaceae); Aculops propinquae (Manson, 1984), comb. nov. on Coprosma propinqua (Rubiaceae); Aculus corynocarpi (Manson, 1984), comb. nov. on Corynocarpus laevigatus (Corynocarpaceae); Aculus heatherae (Manson, 1984), comb. nov. on Raukaua simplex (Araliaceae), Leptospermum scoparium (Myrtaceae) and Syzygium maire (Myrtaceae); Aculus lalithi sp. nov. on Melicope ternate (Rutaceae). A key to the New Zealand species of Eriophyes is provided.